2020
DOI: 10.1177/2045894020941484
|View full text |Cite
|
Sign up to set email alerts
|

Stim‐activated TRPC‐ORAI channels in pulmonary hypertension induced by chronic intermittent hypoxia

Abstract: Obstructive sleep apnea (OSA), a breathing disorder featured by chronic intermittent hypoxia (CIH) is associated with pulmonary hypertension (PH). Rodents exposed to CIH develop pulmonary vascular remodeling and PH, but the pathogenic mechanisms are not well known. Overexpression of Stim-activated Transient Receptor Potential Channels (TRPC) and Calcium Release-Activated Calcium Channel Protein (ORAI) TRPC-ORAI Ca2+ channels (STOC) has been involved in pulmonary vascular remodeling and PH in sustained hypoxia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…STIM1 and Orai1 expression and function were increased in aortas from spontaneously hypertensive rats [ 179 ]. In an experimental obstructive sleep apnea model induced in rats by chronic intermittent hypoxia (CIH) (5% inspired O 2 for 20 s, followed by 280 s of room air, 12 times per hour for 8 h a day for 14 to 28 days), Castillo-Galán et al showed the increased protein expression of Orai1, STIM1, and TRPC1, -C4, -C6 in the lungs of CIH rats [ 180 ]. Treatment of these rats with 2-APB decreased right ventricular systolic pressure (RVSP) and pulmonary vessel remodeling, which increased following CIH exposure [ 181 ].…”
Section: Soce In Pahmentioning
confidence: 99%
“…STIM1 and Orai1 expression and function were increased in aortas from spontaneously hypertensive rats [ 179 ]. In an experimental obstructive sleep apnea model induced in rats by chronic intermittent hypoxia (CIH) (5% inspired O 2 for 20 s, followed by 280 s of room air, 12 times per hour for 8 h a day for 14 to 28 days), Castillo-Galán et al showed the increased protein expression of Orai1, STIM1, and TRPC1, -C4, -C6 in the lungs of CIH rats [ 180 ]. Treatment of these rats with 2-APB decreased right ventricular systolic pressure (RVSP) and pulmonary vessel remodeling, which increased following CIH exposure [ 181 ].…”
Section: Soce In Pahmentioning
confidence: 99%
“…Notably, 20–25 representative resistance pulmonary arteries (150–250 μm of internal diameter) from each animal were selected for these analyses. Vascular density (number of arteries/area), percentage luminal area (luminal area/total area), and the wall, media, and adventitia thicknesses were calculated as described previously ( Herrera et al, 2008b ; Torres et al, 2015 ; Castillo-Galán et al, 2016 ; Castillo-Galan et al, 2020 ). The analysis of the microphotographs was performed with the Image Pro-Plus 6.2 software (Media Cybernetics, Inc., Rockville, MD, United States).…”
Section: Methodsmentioning
confidence: 99%
“…arrhythmia [138] Orai Participation in SOCE [139,140] Pulmonary hypertension [140]; thrombosis [141] STIM SOCE activation [142] Hypertension and atherosclerosis [143][144][145];…”
Section: Cross-talk Between Mechanosensitive Ion Channels and Ca 2+ Regulatory Proteins In Cardiovascular Systemmentioning
confidence: 99%
“…When the EF-hand of STIM1 is mutated, it spontaneously aggregates with TRPC1 and then activates TRPC1 [159]. The interaction between TRP and STIM is implicated in the progression of many diseases, particularly some cardiovascular diseases such as arterial hypertension, atherosclerosis, or thrombosis [141,[143][144][145][146].…”
Section: Trp and Stimmentioning
confidence: 99%